2023
DOI: 10.1007/s11250-023-03458-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the chemical composition and nutritional value of forage resources in Colombia with methane emissions by enteric fermentation

Abstract: In the livestock sector, strategies are available to mitigate gas emissions, such as methane, one of the alternatives that have shown potential correspondence to changes in the composition of the diet. The main aim of this study was to analyze the influence of methane emissions with data on enteric fermentation obtained from the Electronic Data Gathering, Analysis, and Retrieval (EDGAR) database and based on forecasts of methane emissions by enteric fermentation with an autoregressive integrated moving average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The chemical composition, especially the dry matter and fibre content, as well as the digestibility present in feed, is directly related to the production of enteric CH 4 by ruminants [25]. Some researchers suggest increasing the intake of more digestible forages as the main measure to mitigate CH 4 emissions [7].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition, especially the dry matter and fibre content, as well as the digestibility present in feed, is directly related to the production of enteric CH 4 by ruminants [25]. Some researchers suggest increasing the intake of more digestible forages as the main measure to mitigate CH 4 emissions [7].…”
Section: Discussionmentioning
confidence: 99%
“…[54] also reported that there were high correlations of (p < 0.05) ADF with cellulose, ADL with ADF and NDF with HC. In [68], the authors also indicated that there was a positive correlation between ash, NDF and ADF. The hierarchical cluster analysis highlighted an overall pattern of genetic diversity and the relationship between cultivars.…”
Section: Pearson's Correlation Coefficient Between Parametersmentioning
confidence: 95%
“…Emerging nations have increased alert levels for urban air pollution in their main cities globally. Air pollution can come from many sources of emission, both natural and anthropogenic, including industrial processes, power generation [1], vehicles emissions [2], agricultural activities [3,4], burning forests [5], sea aerosols [6], and biogenic emissions [7], among others. In earlier studies such as those carried out by Sunil Gulia et al [8], the scientific evidence regarding air pollution's health impact and data on air quality have been considered for inclusion in the recommendations of the WHO Global Air Quality Guidelines about the primary pollutants responsible for urban air quality deterioration.…”
Section: Introductionmentioning
confidence: 99%